Oscillator Strength and Intensity Parameters of Sm(III), Ho(III) and Er(III) Metal Complexes with Some Schiff Base Ligand - Arora, Atul; Sharma, Anu; Mathur, Kirty; Mathur, R.P. (Asian Journal of Chemistry, 2010)
The absorption spectra of Schiff base ligands, o-(α-benzoylmethylbenzylideneimino) benzoic acid (H2AD), o-(α-2-oxopropylbenzylideneimino) benzoic acid (H2AB), o-(α-2-oxopentylideneimino) benzoic acid (H2AA), 2-(α-benzoyl methylbenzylideneimino) propanoic acid (H2BD), 2-(α-2-oxopropylbenzylideneimino) propanoic acid (H2BB) and 3-(α-2-oxopentylideneimino) propanoic acid (H2BA) with Sm(Ill), Ho(lII) and Er(Ill) ions have been studied in different metal-ligand stoichiometry in 20% dioxane-water medium. The oscillator strengths for the 4f-4f multiplet to multiplet transitions are empirically determined from the absorption spectra The intensity parameters T λ (λ = 2, 4, 6) for all the complexes were evaluated by applying the Judd-Ofelt theorem to the observed oscillator strengths. The values of the intensity parameters are compared and discussed to investigate the sensitivity of the intensity parameters to the ligand environment.